Continuous flow synthesis of hypercrosslinked polymers (HCPs) and its environmental impact evaluation - Chanchaona, Nadhita (The University of Edinburgh, 2024)
Hypercrosslinked polymers(HCPs) are a class of microporous adsorbents with a wide range of applications, including dye adsorption, and gas storage. Traditionally, HCPs are synthesised through Friedel-Crafts alkylation, which involves a time-consuming synthesis process in batch reactors, posing challenges for scaling up production to meet global demand. The prolong reaction duration issue could be eliminated by means of a new synthetic method to substitute batch reactors. The ultimate aim of this study is to intensify the HCP synthesis process by transitioning from batch reactors to continuous reactors. This shift intents to enhance productivity while maintaining a high specific surface area, crucial for superior adsorption capacity. Additionally, this study aspired to reduce the environmental impact associated with this new method for HCP synthesis. To achieve these objectives, a continuous flow system had been adopted as a replacement for the conventional batch method in HCP synthesis. Three types of HCPs were successfully synthesised using well-established strategies (internally crosslinked, post-crosslinked, and externally crosslinked) in the continuous flow system, showcasing its versatility. The productivity, measured as space-time-yield (STY), of continuous flow synthesis showed an enhancement ranging from 32 – 117-fold when compared to batch synthesis. These improvements were attributed to reducing reaction duration during flow synthesis, from 1440 minutes (24 hours) to 5 – 15 minutes. The specific surface areas of flow-synthesised HCPs were, on average, lower than the batch-synthesised HCPs by 1.5 – 10 %. This meant that when compared to batch-synthesised HCPs, more quantities of flow-synthesised HCPs were needed for dye adsorption and CO2 capture. However, despite this requirement for larger quantities, the environmental assessment of continuous flow synthesis indicated a reduction in negative environmental impacts across most environmental impact indicators. This suggest an improvement in the environmental sustainability of continuous flow HCP synthesis compared to batch synthesis. Furthermore, this study also explored an alternative synthesis method using twin screw extraction (TSE) with deep eutectic solvents (DES), a benign solvent replacement for halogenated solvents, during HCP synthesis. Although this approach offers promising potential as the replacement of continuous flow synthesis using conventional halogenated solvents, further investigations are warranted for its optimisation. In conclusion, this thesis advocates for the adoption of continuous flow synthesis of HCPs, underlining its potential for productivity enhancement and reduced environmental impacts. This study lays the foundation for the potential industrial-scale implementation of continuous flow synthesis, bridging the gap between HCP supply and demand while contributing to lower environmental impacts in the production process.
Keywords: hypercrosslinked polymers; water treatment; HCPs; continuous flow reactors; HCP synthesis; twin screw extrusion; efficiency